Feasibility and safety of combined laparoscopic and transvaginal oocyte retrieval in a woman with vaginal recurrence of cervical adenocarcinoma: a case report - Ingold, Caroline; Navarro, Paula Andrea; de Oliveira, Renato; Barbosa, Caio Parente; Sadalla, José Carlos; Bedoschi, Giuliano (Frontiers in Reproductive Health, 2024)
Introduction: Oocyte cryopreservation is an established technique for fertility preservation in women diagnosed with cancer. However, some clinical scenarios may preclude the commonly used transvaginal approach to oocyte retrieval. In such cases, a laparoscopic approach may be required. Here, we report the feasibility and safety of a combined laparoscopic and transvaginal approach for oocyte retrieval in a woman with vaginal recurrence of cervical adenocarcinoma. This approach allowed for oocyte cryopreservation prior to cancer treatment, representing a novel application in this clinical context. Methods: A 31-year-old woman with endocervical adenocarcinoma underwent laparoscopic radical hysterectomy and pelvic lymph node dissection. She presented with vaginal recurrence and was referred for fertility preservation by oocyte cryopreservation before chemotherapy and radiotherapy/brachytherapy. Ovarian stimulation was initiated with a gonadotropin antagonist protocol combined with aromatase inhibitors, and oocyte retrieval was performed with a combined laparoscopic and transvaginal approach.Results: A total of 18 oocytes were retrieved and 10 mature oocytes were cryopreserved. Peritoneal fluid cytology was negative for malignancy. The patient underwent chemotherapy and radiotherapy/brachytherapy and was disease-free after oocyte retrieval.The combined laparoscopic and transvaginal approach for oocyte retrieval emerges as a practical and efficacious method for fertility preservation in cases of cervical adenocarcinoma with vaginal recurrence. Further comprehensive studies are warranted to establish the reproducibility, safety, and long-term outcomes associated with this innovative approach.